2021
DOI: 10.1097/wco.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system tuberculosis

Abstract: Purpose of review Central nervous system (CNS) tuberculosis is the most devastating form of tuberculosis (TB), with mortality and or neurological sequelae in over half of individuals. We reviewed original research and systematic reviews published since 1 January 2019 for new developments in CNS TB pathophysiology, diagnosis, management and prognosis. Recent findings Insight in the pathophysiology is increasing steadily since the landmark studies in 1933… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Small tuberculous lesions known as Rich's foci, formed in the cerebral cortex, cerebral parenchyma, or spinal cord, may remain dormant for several years. Rupture of these foci leads to the spread of the bacilli into the subarachnoid space, resulting in tuberculous meningitis 11 . Risk factors of miliary TB and extrapulmonary TB include HIV, diabetes mellitus, smoking, alcohol abuse, malnutrition, and overcrowding, which were absent in our patient 8,12 .…”
Section: Discussionmentioning
confidence: 74%
“…Small tuberculous lesions known as Rich's foci, formed in the cerebral cortex, cerebral parenchyma, or spinal cord, may remain dormant for several years. Rupture of these foci leads to the spread of the bacilli into the subarachnoid space, resulting in tuberculous meningitis 11 . Risk factors of miliary TB and extrapulmonary TB include HIV, diabetes mellitus, smoking, alcohol abuse, malnutrition, and overcrowding, which were absent in our patient 8,12 .…”
Section: Discussionmentioning
confidence: 74%
“…CNS TB accounts for about 1% of all TB cases and 8% of extrapulmonary TB cases. Their rarity, combined with the complex presentation and management needs during pregnancy, underscores the need for focused research in this area 20 . Historical documentation since 1898 highlights the ongoing challenge of diagnosing and managing brain tumors, including tuberculomas, in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…This is much lower than the 10mg/kg/day dose recommended in the guidelines for the treatment of tuberculosis meningitis in children [4]. Several studies have shown that lower isoniazid exposure or lower dose of isoniazid is associated with a high risk of death in patients with tuberculosis meningitis [5,6], and pharmacokinetic studies suggest increasing isoniazid doses [7]. However, the optimal isoniazid dose recommended to treat adults with tuberculosis meningitis is currently inconclusive.…”
Section: Introductionmentioning
confidence: 99%